Jacobite Explanation of the Trinity in the Context of Muʿtazilite Theology: Abu Raʾitah al-Takriti - Vali Abdi (Religious Inquiries, 2019)
The Melkites, Jacobites, and Nestorians were the main Christian communities under Muslim rule. Several pre-Islamic Arab Christian authors wrote treatises concerning their beliefs in Arabic, some of which date back to the early Islamic centuries. The multiplicity of such polemical works suggests an intellectually open society and a degree of tolerance shown by Muslim leaders. Abu Raʾitah al-Takriti (d. 835) was one of the most influential Jacobite authors, who wrote treatises on the Trinity and Incarnation. His era shows the new challenges raised by Muslim surroundings, some of which were unprecedented in the Christian world. As such, Arab Christians like Abu Raʾitah were compelled to use new methods and respond to novel objections. Abu Raʾitah tried to explain the Trinity in the framework of Islamic theology (kalam). Therefore, he introduced the hypostases as God’s attributes. According to him, Knowledge (Speech) and Life are two substantial and eternal divine attributes. Abu Raʾitah also referred to the Bible and the Quran and used various analogies in order to defend the doctrine of the Trinity.